Effect of temperature and radiation on the physiological response of cacao (Theobroma cacao L): breeding strategies - Baque Zambrano, Elizabeth (2024)
Cocoa (Theobroma cacao L.), has its origin in the Amazon and is usually grown under the shade of trees and or in full sun exposure. This variability in light conditions makes physiological responses different between cocoa cultivars. In the coming decades, an inevitable increase in global temperature is expected. By 2050, it is estimated that in the Latin American tropical region these increases will lead to reductions in precipitation greater than 10%, that is, we will have drier environments, which will undoubtedly affect cocoa cultivation. There is uncertainty in the possible effects of changes in temperature on cocoa due to the lack of information and the few cultivars that have been evaluated. The information collected in this review serves as a basis for understanding the responses of cocoa to light and temperature conditions and it is undeniable that more research is required to achieve a greater understanding of the complexities of climate changes and their effects on cocoa production. One aspect that stands out is a focus on research that must be carried out in field conditions.